1986
DOI: 10.1002/mus.880090907
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide neuropathy: An electrophysiologic study

Abstract: Thalidomide is effective in the treatment of such disabling dermatologic diseases as aphthosis, discoid lupus erythematosus, and prurigo nodularis, in which other drugs fail. However, its use can induce neuropathy necessitating caution in its administration. It was found in this electrophysiologic study of 13 patients that the data best revealing neuropathy, even when clinical abnormalities were not apparent, were reduction of sensory nerve action potential amplitude on the sural nerve, increase of somatosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 26 publications
2
53
1
3
Order By: Relevance
“…As in previous reports, 16,19,27,42,43 the sural SNAP amplitude was the most sensitive neurophysiologic marker of TPN in our study. When the sural response was absent at baseline, we relied on symptoms and the NIS.…”
Section: Commentsupporting
confidence: 72%
See 2 more Smart Citations
“…As in previous reports, 16,19,27,42,43 the sural SNAP amplitude was the most sensitive neurophysiologic marker of TPN in our study. When the sural response was absent at baseline, we relied on symptoms and the NIS.…”
Section: Commentsupporting
confidence: 72%
“…Increased age is suggested as a predisposing factor 42 but was not observed in our study or the study by Basturi-Garin et al 20 Incomplete improvement of the neuropathy with termination of thalidomide treatment supports the view that TPN is a neuronopathy. 18,19,27,43 None of our subjects was disabled by residual neuropathy. Thalidomide can be successfully restarted or reduced without progression of TPN.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, weakness and signs of pyramidal tract involvement may occur. Sensory symptoms may persist, and sometimes get worsen, after withdrawal of the drug and the pathologic findings suggest axonal neuropathy 34 . Although the frequency and the severity of neuropathy are not always found to be related to total dosage 34 , Wulff et al, confirmed that the neuropathy began after a total of 40-50g of thalidomide in most patients 35 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…Electrophysiologic findings include a sensory axon polyneuropathy with a sensory nerve action potential (SNAP) amplitude decrease. A 50% decrease in SNAP amplitude is closely related to clinical signs and symptoms 7,8 Therefore, it is recommended that baseline nerve studies be performed in all patients who receive thalidomide within 3 months of initiating therapy and every 6 months thereafter. With a decrease in SNAP of greater than 30%, more frequent testing is recommended, and thalidomide therapy should be discontinued if the SNAP decreases by more than 50% until the peripheral neuropathy resolves.…”
Section: Commentmentioning
confidence: 99%